Pooling, Saving, and Prevention : A Comprehensive Insurance Approach to Social Risk Management - Packard, Truman (World Bank, Washington, DC, 2012)
Individuals and societies can respond in a variety of ways when faced with the prospect of economic losses from shocks like natural disasters, sickness, sudden death, disability and unemployment. Social risk management is a conceptual framework encompassing three broad categories of response: prevention, mitigation, and coping. The comprehensive Insurance approach focuses on mitigation, offering a tool for determining which insurance instruments and preventive measures will be most effective given the size and frequency of various types of possible economic losses. This article explains the comprehensive insurance framework, and uses it to assess recent reforms in Chile's unemployment insurance system.